2014
DOI: 10.1021/om500044a
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Mechanistic Understanding of Molecular Electrocatalysts for CO2 Reduction using Infrared Spectroelectrochemistry

Abstract: Review: 67 refs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
279
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(311 citation statements)
references
References 62 publications
27
279
4
1
Order By: Relevance
“…The first reduction wave corresponds to a metal-based reduction of the Mn center, which leads to the formation of a Mn−Mn dimer. 37 In MnBr(bpy)(CO) 3 , oxidative cleavage of the metal−metal bond within the corresponding dimer is observed at −0.30 V vs SCE. 12 We similarly find an oxidative wave for this process at ca.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first reduction wave corresponds to a metal-based reduction of the Mn center, which leads to the formation of a Mn−Mn dimer. 37 In MnBr(bpy)(CO) 3 , oxidative cleavage of the metal−metal bond within the corresponding dimer is observed at −0.30 V vs SCE. 12 We similarly find an oxidative wave for this process at ca.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…They reported that, on the basis of cyclic voltammetry and infrared spectroelectrochemistry investigations, a [Mn(bpy)(CO) 3 ] − intermediate serves as the active species for CO 2 reduction with manganese, which is analogous to the proposed pathway for rhenium. 37 Accordingly, we truncated the potential energy surface and considered only the transformation of as a barometer for improved design. Our theoretical investigation began by considering Mn(bpy)(CO) 3 COOH in a CO 2 -saturated acetonitrile environment.…”
Section: ■ Theorymentioning
confidence: 99%
“…10 For some of the Re analogues, a one-electron reduced complex, [ReCl(CO) 3 (R-bpy )] was observed by IR spectroscopy and identified by the ca. 15-20 cm -1 decrease in the (CO) energy, 11,12,13 as was the five-coordinate radical [Re(CO) 3 ( t Bubpy)] by an additional 15-20 cm -1 shift .…”
Section: Abstract: Manganese Tricarbonyl Bromide Complexes Incorporatmentioning
confidence: 99%
“…10 For some of the Re analogues, a one-electron reduced complex, [ReCl(CO) 3 (R-bpy )] was observed by IR spectroscopy and identified by the ca. 15-20 cm -1 decrease in the (CO) energy, 11,12,13 as was the five-coordinate radical [Re(CO) 3 ( t Bubpy)] by an additional 15-20 cm -1 shift .Two mechanisms have been proposed 10,14-18 for the ultimate reduction of [Mn(CO) 3 ( -diimine)] 2 in the presence of CO 2 , which can be referred to as the anionic, and the oxidative addition 19 pathways. The anionic pathway involves reduction of the dimer [Mn(CO) 3 ( -diimine)] 2 at a more negative potential than the parent complex generating the five-coordinate anion [Mn(CO) 3 ( -diimine)] to which CO 2 coordinates and is catalyti-2 cally reduced in the presence of a Brönsted acid (the source of H + ).…”
mentioning
confidence: 99%
“…29,32 In any case, the proposed active species is a doubly reduced anion that possesses a vacant axial site for CO 2 coordination: [Mn(κ 2 -L)(CO) 3 ] − (c, see Scheme 1). Theoretical 38 and experimental 39,40 investigations of the mechanism suggest that oneelectron reduction of the metal center causes the axial ligand, usually a bromide ion, to dissociate. Subsequently, the neutral radical monomer dimerizes to give [Mn(κ 2 -L)(CO) 3 ] 2 (b).…”
Section: ■ Introductionmentioning
confidence: 99%